Membangun karakter anti korupsi melalui pendidikan kewarganegaraan - Rohidussyafiq, Moh (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the role of Civic Education in shaping anti-corruption character among the younger generation. Corruption is a crucial problem that has a significant impact on the social, political, economic, and moral aspects of Indonesian society, thus requiring a prevention strategy through character education. The methodological approach applied in this study is a literature study, by examining various relevant scientific literature sources on anti-corruption education and Civic Education. The results of the study indicate that Civic Education plays an important role in instilling anti-corruption values, such as honesty, responsibility, discipline, and integrity, through the instillation of Pancasila values ​​and character education. Furthermore, school culture and teacher role models are also key determinants in shaping anti-corruption behavior in students. Therefore, Civic Education can serve as an effective instrument in shaping a generation with integrity and a strong anti-corruption awareness.